Analysis of Metagenomics Next Generation Sequence Data for Fungal ITS Barcoding: Do You Need Advance Bioinformatics Experience? - Ahmed, Abdalla (Frontiers in Microbiology, 2016)
During the last few decades, most of microbiology laboratories have become familiar in analyzing Sanger sequence data for ITS barcoding. However, with the availability of next-generation sequencing platforms in many centers, it has become important for medical mycologists to know how to make sense of the massive sequence data generated by these new sequencing technologies. In many reference laboratories, the analysis of such data is not a big deal, since suitable IT infrastructure and well-trained bioinformatics scientists are always available. However, in small research laboratories and clinical microbiology laboratories the availability of such resources are always lacking. In this report, simple and user-friendly bioinformatics work-flow is suggested for fast and reproducible ITS barcoding of fungi.